2017
DOI: 10.1161/strokeaha.116.016360
|View full text |Cite
|
Sign up to set email alerts
|

Transfer to High-Volume Centers Associated With Reduced Mortality After Endovascular Treatment of Acute Stroke

Abstract: We report a beneficial effect of treatment at high-volume hospitals in spite of the detrimental effects of transfer. These findings argue for the centralization of care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
84
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(88 citation statements)
references
References 18 publications
2
84
0
Order By: Relevance
“…Centres with high volume of ECR have a reduced rate of mortality compared to low-volume centres (9.8% compared to 19.7%) [14]. High-volume centres have also been shown to have shorter times from CT to groin puncture, better clinical outcomes and better reperfusion rates in ECR for acute ischaemic stroke due to large vessel occlusion [15].…”
Section: Introductionmentioning
confidence: 99%
“…Centres with high volume of ECR have a reduced rate of mortality compared to low-volume centres (9.8% compared to 19.7%) [14]. High-volume centres have also been shown to have shorter times from CT to groin puncture, better clinical outcomes and better reperfusion rates in ECR for acute ischaemic stroke due to large vessel occlusion [15].…”
Section: Introductionmentioning
confidence: 99%
“…If confirmed, our data suggest that in such a setting scales like the FAST-ED and RACE may be advantageous as they appeared less impervious to leukoaraiosis-related misclassification. Furthermore, LVO scales are increasingly used to render decisions regarding immediate patient transfer to EST capable hospitals when LVO is suspected, 13,21-23 including in the setting of telemedicine consultations. 24 In this setting our results may be impactful when a plain head CT is reviewed (and provide information on leukoaraiosis severity) but no CTA obtained due to lack of resources, immediate availability, or because it is undesirable to avoid repeat imaging at the EST-capable hub hospital.…”
Section: Discussionmentioning
confidence: 99%
“…The best option for the management of AIS is to have patients transferred to and treated in high volume, level 1 centers, as demonstrated by scientific evidence 15. However, in some situations, specifically due to geographical, traffic, and transportation conditions, access of patients to such centers in an acceptable time frame may not be possible.…”
Section: Purposementioning
confidence: 99%
“…It has been shown that high volume centers have a significantly lower mortality, even if the patient has to be transferred from a low volume center. Rinaldo et al found that centers performing 35 or more thrombectomy cases per year would classify as ‘high volume’ and offer the lowest mortality rate for patients 15. Similarly, the American College of Cardiology Foundation, the American Heart Association , and the Society for Cardiovascular Angiography and Interventions suggest a minimum of 36 percutaneous coronary interventions for acute myocardial infarction per year per center as a minimum requirement 17…”
Section: Level 2 Center: Standards Of Practicementioning
confidence: 99%